Effect of Natural Hazards on the Income and Sense of Subjective Well-Being of Rural Residents: Evidence From Rural China - Huang, Lei (Frontiers in Ecology and Evolution, 2022)
China is a country that experiences severe natural hazards. In comparison to urban residents, farmers in rural areas of China are more susceptible to these natural hazards, whose impact is multidimensional; however, existing research has mainly focused on the household level. Based on China Household Finance Survey (CHFS) data in 2019, a total of 17,900 farmer households have been chosen to discuss the influences of natural hazards on the rural income and subjective well-being from the individual perspective and the family perspective; further, regional differences within the sphere of influence have been analyzed. Empirical results demonstrate that (1) the farmer household income is a factor that affects subjective well-being, but does not play a decisive role. (2) From the perspective of spatial differences and laws, subjective well-being and the income of farmers vary significantly. The subjective well-being in North China (NC) is the highest, while the subjective well-being in the Central South (CS) is the lowest. The distribution trend of rural income is high in Southeast China (SE) and low in Northwest China (NW). (3) Natural hazards can lower the subjective well-being (Mean ATT=-0.1040) and income (Mean ATT=-0.1715) of farmers significantly. Moreover, the influences of natural hazards on subjective well-being are lower than that on income. Therefore, it is imperative to ascertain the impact of natural hazards on farmers’ subjective well-being and household income. Further, the government should consider regional differences and the different affected groups, and also strengthen the farmers’ ability to cope with hazards and their post-hazard recovery ability during the implementation of hazard rescue.